THE ANALYSIS OF FLOUTING OF MAXIM IN KONG SKULL ISLAND MOVIE - Anak Agung Intan Apriyani; I Putu Gede Satria Wiraharja (Universitas Warmadewa, 2023)
The aims of this study is to analyze the types of flouting of maxim found in Kong Skull island movie and to identify the reasons behind the flouting of maxim since it is very important in order to make the communication as effective as possible. In this study, the researcher used a theory proposed by Grice (1975) in analyzing the types of flouting of maxim and a theory proposed by Leech (1983) in analyzing the reason behind the flouting of maxim occurs in the movie. This study used both formal and informal methods in providing the deeper understanding regarding to the flouting of maxim and the reasons of flouting. The data were collected from the conversation occurred among the characters in Kong Skull Island movie and qualitative method was applied in the research. The data were collected through observation and note taking technique. The finding showed that flouting maxim occurred 30 times, they were flouting maxim of quantity 14 times (46,67%), flouting maxim of quality 4 times (13,33%), flouting maxim of relation 9 times (30,00%) and flouting maxim of manner 3 times (10,00%). The reason of flouting maxim found with frequency; competitive reason 6 times (20,00%), convivial reason 1 time (3,33%), collaborative reason 19 times (63,33%) and conflictive reason 4 times (13,34%). To sum up, the researcher found that the most types of maxim flouted by the characters in the movie is flouting maxim of quantity and the most types of reason behind the flouting maxim is collaborative reason. Keywords: cooperative principle, flouting maxim, reason of flouting maxim